1994
DOI: 10.1063/1.466649
|View full text |Cite
|
Sign up to set email alerts
|

Direct measurement of thermal rate constants for state-to-state rotational energy transfer in collisions of CN(X 2Σ+, v=2, N) with He

Abstract: Stimulated emission pumping state preparation and laser induced fluorescence state detection in the CN(B 2Σ+–X 2Σ+) violet system have been employed to study relaxation of single rotational states of CN(X 2Σ+, v=2) in collisions with He at 295 K. Approximately 2/3 of the value of the total removal rate constant for CN(X 2Σ+, v=2, N=2, 11, or 14) corresponds to changes in the rotational quantum number of ‖ΔN‖≤3 and a strong propensity is evident which favors even changes in N for ‖ΔN‖≤4. The measured rate const… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
20
1

Year Published

1995
1995
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(26 citation statements)
references
References 40 publications
5
20
1
Order By: Relevance
“…CN-He rate coefficients obtained from this PES were found to be in excellent agreement with the experimental rotational (with unresolved fine and hyperfine structure) rate coefficients of Fei et al (1994). This agreement demonstrate the accuracy of the PES and suggests that the rate coefficients obtained from this potential will be accurate enough to allow for improved astrophysical modelling of the ISM.…”
Section: Appendix A: Inelastic Rate Coefficients For the Cn Isotopolosupporting
confidence: 70%
“…CN-He rate coefficients obtained from this PES were found to be in excellent agreement with the experimental rotational (with unresolved fine and hyperfine structure) rate coefficients of Fei et al (1994). This agreement demonstrate the accuracy of the PES and suggests that the rate coefficients obtained from this potential will be accurate enough to allow for improved astrophysical modelling of the ISM.…”
Section: Appendix A: Inelastic Rate Coefficients For the Cn Isotopolosupporting
confidence: 70%
“…Andresen et al observed this interference first in experiments on Ar-NO(X) collisions. 30,31 Similar structure also appears in later data on NO(X), 32,33 NO(A), 32 CN(X), 34 and CN(A) [35][36][37] collisions. The interference oscillations do not change rapidly as the collision energy changes, so they are fairly robust toward experimental averages over collision energy.…”
Section: Introductionsupporting
confidence: 56%
“…Collisions of these Σ molecular electronic states require only a single potential energy surface (PES) to describe the interaction with a collision partner. Fei et al 5,6 have employed stimulated emission pumping to prepare specific initial rotational levels in the CN(X 2 Σ + , V ) 2) vibrational manifold in studies of rotational energy transfer in collisions with He and Ar. Smith and co-workers [7][8][9] have employed IR-visible double resonance to determine total removal and state-to-state rate constants for collisions of selected CN(X 2 Σ + , V ) 2) rotational levels with N 2 and C 2 H 2 .…”
Section: Introductionmentioning
confidence: 99%